A PMUs placement methodology based on inverse of connectivity and critical measurements. (June 2015) - Alvarez, M.J.; Sellschopp, F.S.; Vazquez, E.
Highlights: Method for PMU placement uses logical decisions and arithmetic operations. Results are as good as those who use stochastics and metaheuristics optimization. Advantages such as handling huge networks, quickness, and easiness of programming. It can be expanded for typical meters with PMUs, loss of transmission lines and PMUs. Abstract: This paper presents a methodology to determine the optimal location of phasor measurement units (PMUs) in any network to make it observable. This proposed methodology is based on network connectivity information and unreachability index (URI), where URI is the difficulty to observe any node in the network and it is computed using the inverse of connectivity. In order to choose the optimal bus, it is basically considered to observe a low connectivity bus from an adjacent bus selected by weighting factors that are based on logical analysis of the observability theory combined with the URI; this process stops until the network is observable. The purpose is minimize the number of PMUs in a network with the optimal location and the aim to get a low number of critical measurements (CM) with a high total redundancy (TR), in order to obtain an optimal distribution of PMUs on the network. The proposal is considered as an easy solver for PMU's placing on the network due to important reduction in complexity and computational cost, besides comparable results are as good as those papers using recent optimization methods such as metaheuristics and stochastics, without taking into account that the proposal can handle huge networks. The algorithm is applied to the IEEE 14, 30, 57, 118 and 300-bus systems, and also to medium and large power systems of 1006, 3305, 15, 000, 20, 000 and 30, 000 buses with success.